2022
DOI: 10.1002/1873-3468.14462
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial enzyme FAHD1 regulates complex II activity in breast cancer cells and is indispensable for basal BT‐20 cells in vitro

Abstract: The mitochondrial enzyme fumarylacetoacetate hydrolase domain-containing protein 1 (FAHD1) was identified to be upregulated in breast cancer tissues. Here, we show that FAHD1 is indispensable for the survival of BT-20 cells, representing the basal breast cancer cell type. A lentiviral knock-down of FAHD1 in the breast cancer cell lines MCF-7 and BT-20 results in lower succinate dehydrogenase (complex II) activity. In luminal MCF-7 cells, this leads to reduced proliferation when cultured in medium containing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Remarkably, discrepancies in ROS levels and other data are only apparent when normalized to mitochondrial copy numbers. Similar findings were observed when examining the impact of FAHD1 depletion in breast cancer cells 22 . Consequently, our data indicates that cells compensate for mitochondrial disruptions resulting from either the loss or elevation of FAHD1 levels by increasing mitochondrial numbers.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Remarkably, discrepancies in ROS levels and other data are only apparent when normalized to mitochondrial copy numbers. Similar findings were observed when examining the impact of FAHD1 depletion in breast cancer cells 22 . Consequently, our data indicates that cells compensate for mitochondrial disruptions resulting from either the loss or elevation of FAHD1 levels by increasing mitochondrial numbers.…”
Section: Discussionsupporting
confidence: 83%
“…Connected to this, the malic enzyme (ME) couples mitochondria with aerobic glycolysis, especially in osteoblasts 49 . Of interest, previous studies on FAHD1 knockdown in breast cancer cells also observed regulations in GLS 22 . While a downregulation of KGA was observed in U2OS cells overexpressing the FAHD1 wildtype, an upregulation was noted in U2OS cells overexpressing the T192S variant.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations